2022
DOI: 10.3389/fpsyg.2022.995232
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of psychoeducational resources for adult carers to emotionally support young people impacted by wars: A community case study

Abstract: Wars and armed conflicts have a devastating impact at the economic, social, and individual level. Millions of children and adolescents are forced to bear their disastrous consequences, also in terms of mental health. Their effects are even more complicated when intertwined with those of other disasters such as the current COVID-19 pandemic. To help them face such adverse events, lay adults can be supported by psychoeducational interventions involving simple tools to assist children and adolescents emotionally.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The two maladaptive strategies were, for competence: helplessness and escape; for relatedness: delegation and social isolation; and for autonomy: submission and opposition. These strategies are typically activated in the face of perceived challenges or threats (for a more detailed description, see Zimmer‐Gembeck & Skinner, 2011; for applications, see Burro et al, 2021; Raccanello, Vicentini, Rocca, et al, 2020, Raccanello et al, 2021; Vicentini, Burro, et al, 2022). A meta‐analysis of data on natural disasters indicated that for children and adolescents, strategies such as problem solving and support seeking are positively associated with indicators of wellbeing, while strategies such as escape, delegation, social isolation, and opposition are positively associated with traumatic symptoms (Raccanello et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The two maladaptive strategies were, for competence: helplessness and escape; for relatedness: delegation and social isolation; and for autonomy: submission and opposition. These strategies are typically activated in the face of perceived challenges or threats (for a more detailed description, see Zimmer‐Gembeck & Skinner, 2011; for applications, see Burro et al, 2021; Raccanello, Vicentini, Rocca, et al, 2020, Raccanello et al, 2021; Vicentini, Burro, et al, 2022). A meta‐analysis of data on natural disasters indicated that for children and adolescents, strategies such as problem solving and support seeking are positively associated with indicators of wellbeing, while strategies such as escape, delegation, social isolation, and opposition are positively associated with traumatic symptoms (Raccanello et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is worth anticipating that there is a wide variety of strategies that people can use and that a key factor associated with their efficacy is the ability to flexibly choose the most adequate strategy in relation to the characteristics of both individuals and specific contexts ( Ewert et al, 2021 ; Zimmer-Gembeck, 2021 ). Aiming to elaborate an extended taxonomy that could comprise most of the coping strategies studied within the psychological literature, Skinner and Zimmer-Gembeck ( Zimmer-Gembeck and Skinner, 2011 ; Skinner and Zimmer-Gembeck, 2016 ; Zimmer-Gembeck, 2021 —for adaptation of this categorization to natural disasters, see Raccanello et al, 2020 , 2021 , 2023 ; to the pandemic, see Burro et al, 2021 ; to wars, see Vicentini et al, 2022 ) proposed a classification based on the concept that an uncertain or stressful event can be perceived as a threat or as a challenge towards the three basic human needs for competence, relatedness, and autonomy ( Deci and Ryan, 1985 ). These three needs are at the core of the Self-Determination Theory, according to which individuals’ wellbeing and psychological functioning is associated with the satisfaction (and the absence of frustration) of such needs ( Deci and Ryan, 1985 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Assessing the impact of a crisis situation on mental health provides a basis for developing disaster interventions [46]. It should be noted that research on the indirect consequences of the war in Ukraine is scarce, and thus, the experience of interventions for people affected by other disasters (COVID-19 pandemic, earthquakes) is valuable [47][48][49].…”
Section: Practical Implicationsmentioning
confidence: 99%